KONDISI PERUSAHAAN PERIKANAN DI KOTA BITUNG PASCA MORATORIUM 2014 - Sarempaa, Evan Sparta; Mantjoro, Eddy; Lumenta, Vonne (Universitas Sam Ratulangi, 2017)
AbstractNorth Sulawesi is one of the provinces in Indonesia which have large fisheries potential. The province has made the results of operations and marine fisheries as one of the featured products to spur increase revenue. Then formulated some questions that become problems in this study 1). How is the post-moratorium fishing company in Bitung 2). Is this moratorium policy implementation can enhance the progress of the fishing company in Bitung 3). How do enterprise solutions to meet the needs of the company, when applied moratorium on fishing in Bitung.This study aims to 1) .To obtain scientific data about the condition of the fishing company Post moratorium on fishing in Bitung 2) .To determine the effect of the implementation of the moratorium policy of the condition of the fishing company in Bitung. The method used in this research case study approach. Retrieval of data taken in two fishing companies, namely PT. Sari Tuna Makmur and PT. Blue Ocean Grace International in Bitung City District of Aertembaga, data collection is done by observation and in-depth interviews. 1.Conditions fishing company in Bitung post-moratorium by the Minister of Marine and Fisheries in November 2014 are as follows: a) The number of vessels decreased from 3,213 in 2014 to 2,222 in 2015 and then rose to 3,165 in 2016. b) Production of fish reduced from 111,315.53 in 2014 to 45208.52 in 2015 then production rises, namely 46522.77 2016. c) The increase in the market price of skipjack Winenet, Girian and TPI of the normal price 12500-14000, in 2014 rose to 17000-20000 in 2015 and 2016. As for the Tuna from the standard price of 32000-35000 in 2014 and rose to 50000-55000 in 2015 and 2016. Then for the fish Deho from 5000-8000 at the normal price in 2014, rose to 9000-12000 in 2015, and rose to 12,000-15,000 in 2016. d) Increased export of fishery company PT. STM of 196,034.50 in 2014 to 294,911.4 in 2015 and falling back to 200,403.95 in 2016. e) The increase in exports of fishery company PT. Bogi of 116,196.20 in 2015 to 285,797.3 in 2016. 2. Moratorium Policy turn out to be a positive impact on the company's progress fishery indicated by the decline in the economic sector in Bitung. 3. It was not able to improve the progress of the fishing company in the city of Bitung in general and in particular. 1. moratorium greatly affect the fishing company therefore Policy Minister about the moratorium should be revoked. 2. This study still needs further research is therefore suggested that interested readers can conduct advanced research.Keywords: fisheries, companies, moratorium, conditions